Perancangan User Interface dan User Experience untuk Platform Kursus Online Menggunakan Metode Design Thinking dan Lean UX - Nurmalasari, Elis; Nugroho, Imam Maruf; Totohendarto, Moch. Hafid (UNIKA Santo Thomas, 2023)
XYZ writing community is a community that was formed virtually in 2018 in Jember,East Java. The XYZ Writing Community conducts routine activities, namely holdingclasses on writing every one week twice through the WhatsApp chat platform only.From this problem, it can be seen that the learning system is less effective so that acontainer is needed to accommodate this. Making UI and UX designs will be donefirst using the Design thinking and Lean UX methods. The design results will be testedusing the User Experience Quisionnaerie (UEQ) method. Based on the design methodand testing method used to conduct this research. The distribution of questionnaires atthe Test stage of design thinking to 20 respondents obtained the results of designing anonline course website design in the field of writing using the UEQ method is aboveaverage with a